The Effect of Distribution Channels and Prices on Buying Interest - Siske Anani; Darman Darman; Ramdan Zulkarnain S Dai (West Science Social and Humanities Studies, 2023)
This research was conducted to determine the influence of Distribution Channels and Prices on Gorontalo Typical Yellow Rice Buying Interest. The sampling technique used was Accidental Sampling by determining 62 respondents. The research method uses quantitative descriptive with the Statical program for social science (SPSS). The results of this study showed that Distribution Channel and Price did not significantly affect the Buying Interest of Gorontalo typical yellow rice with a calculated F value of 2.915 and Sig of 0.062, with an influence of 0.090 or 9.0%. The distribution channel does not have a significant effect on the Buying Interest of Gorontalo yellow rice with a calculated value of 1.102 and Sig of 0.275, the price has a significant effect on the Buying Interest of Gorontalo yellow rice with a calculated value of 2.167 and Sig of 0.034.